Antenatal caregiving representations and perinatal behavior in mothers with severe lifetime psychopathology. Issue 1 (2nd September 2019) - Røhder, Katrine; MacBeth, Angus; Agnete Davidsen, Kirstine; Gumley, Andrew; Brennan, Jessica; George, Carol; Harder, Susanne
ABSTRACT: Psychopathology poses a risk for optimal parenting. The current study explored antenatal caregiving representations as markers for later risk of nonoptimal maternal behavior among mothers with severe mental illness. Sixty‐five mothers diagnosed with psychosis, bipolar disorder, depression (psychopathology group), and nonclinical controls participated in a longitudinal study from pregnancy to 16 weeks after birth. Mental health diagnoses and caregiving representations were assessed during pregnancy. Maternal behavior was assessed during the 5‐min recovery phase of the still‐face paradigm at 16 weeks. Mothers with psychopathology reported significantly higher levels of "heightened" caregiving representations (i.e., separation anxiety from the child) than did controls. The only significant diagnostic group difference in perinatal maternal behavior was that mothers diagnosed with depression exhibited more overriding‐intrusive behavior than did nonclinical control mothers. Regression modeling results showed that antenatal caregiving representations of "role reversal" predicted significantly lower levels of sensitivity and higher levels of overriding‐intrusive behavior independent of the effect of psychopathology. The findings can be interpreted in the context of representational transformation to motherhood during pregnancy. The results provide preliminary evidence for the potential of a new questionnaire measure of caregiving representations as a screening instrument for antenatal representational risk. RESUMEN: La sicopatología presenta un riesgo para la crianza óptima. El presente estudio exploró las representaciones antenatales de la prestación de cuidado como señales para un posterior riesgo de conducta materna no óptima entre madres con una enfermedad mental severa. Sesenta y cinco madres con diagnosis de sicosis, trastorno bipolar, depresión (grupo de sicopatología), así como madres en el grupo control no clínico participaron en un estudio longitudinal desde el embarazo hasta 16 semanas después del nacimiento. Se evaluaron los diagnósticos de salud mental y las representaciones de la prestación de cuidado durante el embarazo. La conducta materna fue evaluada durante la fase de cinco minutos de recuperación del paradigma de la Cara Inmóvil a las 16 semanas. Las madres con sicopatología reportaron niveles significativamente más altos de representaciones "agudizadas" de la prestación de cuidado (v.g. ansiedad de estar separadas de su niño) que las madres del grupo de control. La única significativa diferencia de grupo de diagnóstico en cuanto a la conducta materna perinatal fue que las madres con diagnosis de depresión presentaron una conducta predominantemente más intrusa que las madres del grupo de control no clínico. Los resultados del uso de modelos de regresión mostraron que las representaciones antenatales de la prestación de cuidado en cuanto al 'cambio de roles' predijeron niveles significativamente más bajos de sensibilidad y niveles más altos de conductas predominantemente intrusas, independiente del efecto de la sicopatología. Se pueden interpretar los resultados en el contexto de la transformación de representación hacia la maternidad durante el embarazo. Los resultados aportan evidencia preliminar para la posibilidad de una nueva medida de cuestionario sobre las representaciones de la prestación de cuidado como instrumento de detección del riesgo de la representación antenatal. RÉSUMÉ: La psychopathologie pose un risque pour le parentage optimal. Cette étude a exploré les représentations de soin anténatal en tant que marqueurs de risque ultérieur de comportement maternel non‐optimal chez les mères atteintes d'une maladie mentale sérieuse. Soixante‐cinq mères ayant été diagnostiquées avec une psychose, un trouble maniaco‐dépressif, une dépression (groupe psychopathologie) et des contrôles non‐cliniques ont participé à une étude longitudinale de la grossesse à 16 semaines après la naissance. Les diagnostics de santé mentale et les représentations de soin ont été évaluées durant la grossesse. Le comportement maternel a été évalué durant la phase de récupération de cinq minutes du paradigme de Visage Immobile à 16 semaines. Les mères avec une psychopathologie ont fait état de niveaux bien plus élevés de représentations 'accrues' de soin (anxiété de séparation d'avec l'enfant) que les contrôles. La seule différence importante de diagnostic de groupe dans le comportement maternel périnatal était que les mères diagnostiquées avec une dépression ont fait preuve de plus de comportement prépondérant‐intrusif que les mères du groupe de contrôle non‐clinique. Les résultats du modèle de régression ont montré que les représentations anténatales de soin de 'l'inversion des rôles' ont prédit des niveaux de sensibilité bien plus bas et des niveaux de comportement prépondérant‐intrusif bien plus élevés quel que soit l'effet de la psychopathologie. Les résultats peuvent être interprétés dans le contexte de la transformation représentationnelle de la maternité durant la grossesse. Les résultats offrent des preuves préliminaires quant au potentiel d'un nouveau questionnaire comme mesure de représentations de soin en tant qu'instrument de dépistage du risque représentationnel anténatal. ZUSAMMENFASSUNG: Vorgeburtliche Repräsentationen von Fürsorge und perinatales Verhalten bei Müttern mit schwerer, lebenslanger Psychopathologie Psychopathologie birgt ein Risiko für optimale Elternschaft. Die vorliegende Studie untersuchte vorgeburtliche Repräsentationen von Fürsorge als Marker für das spätere Risiko eines nicht optimalen mütterlichen Verhaltens bei Müttern mit schweren psychischen Erkrankungen. 65 Mütter, bei denen Psychose, bipolare Störung oder Depression diagnostiziert wurden, (psychopathologische Gruppe) und eine nichtklinische Kontrollgruppe nahmen an einer Längsschnittstudie von der Schwangerschaft bis 16 Wochen nach der Geburt teil. Während der Schwangerschaft wurden die Diagnosen der psychischen Erkrankungen und Repräsentationen von Fürsorge erhoben. 16 Wochen nach der Geburt wurde das Verhalten der Mütter während der fünfminütigen Erholungsphase des „Still‐Face‐Paradigmas" beobachtet. Bei Müttern mit Psychopathologie zeigten sich signifikant höhere Werte von „erhöhten" Repräsentationen von Fürsorge (d.h. Trennungsangst vom Kind) als bei der Kontrollgruppe. Der einzige signifikante diagnostische Gruppenunterschied im perinatalen Verhalten der Mütter bestand darin, dass Mütter, bei denen eine Depression diagnostiziert wurde, mehr übersteuerndes‐intrusives Verhalten zeigten als nicht‐klinische Kontrollmütter. Eine Regressionsanalyse ergab, dass vorgeburtliche Fürsorgerepräsentationen von „Rollentausch„ unabhängig von der Ausprägung der Psychopathologie ein signifikant geringeres Maß an Sensitivität und ein höheres Maß an übersteuerndem‐intrusivem Verhalten vorhersagten. Die Ergebnisse können im Kontext der Transformation von Repräsentationen zur Mutterschaft während der Schwangerschaft interpretiert werden. Die Ergebnisse liefern vorläufige Belege für das Potenzial eines neuen Fragebogens als Screeninginstrument für das Risiko, das von vorgeburtlichen Repräsentationen ausgehen kann. 抄録: 生涯にわたる重度の精神病理を抱えた母親の出産前の育児表象と出産後の行動 精神病理は適切な育児にとってのリスクとなり得る。本研究では、重度の精神疾患を持つ母親の適切でない母親行動の後のリスクマーカーとしての出産前の育児表象について探究した。精神病、双極性障害、うつ病と診断された 65 人の母親 (精神病理を持つグループ) と、臨床的に問題の無いコントロール群が妊娠期から出産後 16 週の期間における縦断的研究に参加した。精神保健的診断と育児表象は妊娠期間中に評価された。母親の行動は 16 週の時点における Still Face 実験による 5 分間の回復期を用いて評価された。 精神病理を背景に持つ母親たちは、コントロール群と比べて明らかに高いレベルの「緊張した」育児表象 (例; 子どもからの分離不安) を報告した。出産後の母親の行動における診断グループ有意差は、うつ病と診断された母親たちが臨床的に問題の無いコントロール群の母親に比べて過度に侵入的な行動を示した点のみであった。回帰モデルの結果は、出生前の役割逆転の育児表象から、明らかにより低いレベルの感受性と高いレベルの過度の侵入性が精神病理の影響とは独立して予測されることを示した。これらの所見は妊娠期の母性への表象的移行の流れにおいて見て取れる。これらの結果は出生前の表象的リスクのスクリーニングの方法のひとつとして、新しい育児表象の質問調査が今後にむけて可能性をもつことを示す。 摘要: 患有嚴重終生精神疾病母親的產前護理表現和圍產期行為 精神疾病帶來優質育兒的風險。本研究探索產前護理的表現形式, 作為患有嚴重精神疾病的母親以後的非優質母親行為風險的標誌。 65 名被診斷出患有精神病丶躁鬱症丶抑鬱症 (精神病理學組) 和非臨床對照組的母親參加從懷孕到出生後 16 週的縱向研究。研究在懷孕期間評估心理健康和護理表現。在 16 週的 Still Face 範例的五分鐘恢復階段中評估母親行為。患有精神疾病學的母親報告顯, "高度緊張" 的護理表徵水平 (即與孩子的分離焦慮) 明顯高於對照組。圍產期母親行為的唯一顯著診斷組差異是, 被診斷患有抑鬱症的母親比非臨床對照組母親表現出更多的壓倒侵入行為。回歸模型分析的結果表明, "角色逆轉" 的產前護理表徵, 預測顯著較低的敏感度和較高的壓倒侵入行為, 獨立於精神疾病的影響。這些發現可以在懷孕期間轉變為母親的情況下得到解釋。結果提供了初步證據, 證明一項新的調查護理表徵問卷, 作為產前代表性風險篩查工具的潛力。 ملخص: التمثيلات الذهنية للرعاية قبل الولادة والسلوك في فتره ما قبل الولادة عند الأمهات ذوات الاعتلال النفسي الشديد الأمراض النفسية تشكل خطرا علي تقديم الرعاية الوالدية المثلى. وقد استطلعت الدراسة الحالية التمثيلات المتعلقة برعاية الحوامل كعلامات لخطر السلوك الأمومي غير الأمثل فيما بعد بين الأمهات ذوات الامراض النفسية الحادة. اشترك في الدراسة 65 من الأمهات المصابات بالذهان ، والاضطراب ثنائي القطب ، والاكتئاب ، وكانت دراسة طولية من الحمل إلى 16 أسبوعا بعد الولادة. وتم تقييم التشخيصات الصحية النفسية وتمثيلات الرعاية اثناء الحمل. كما تم تقييم السلوك الأمومي اثناء مرحله التعافي التي استمرت خمس دقائق في نموذج "الوجه الثابت" عند 16 أسبوعا. وأبلغت الأمهات ذوات الامراض النفسية عن مستويات أعلي بكثير من التمثيلات ' المبالغ فيها ' للرعاية (اي قلق الانفصال عن الطفل) من المجموعة الضابطة. وكان الفرق الوحيد الدال احصائيا في السلوك الأمومي في الولادة ان الأمهات المشخصات بالاكتئاب أظهرن سلوك أكثر "هيمنة تدخلية" من الأمهات في المجموعة الضابطة. وأظهرت نتائج نمذجة الانحدار ان تمثيلات الرعاية قبل الولادة الخاصة بـ "انعكاس الدور" تنبأت بمستويات اقل بكثير من الحساسية ومستويات اعلي من سلوك الهيمنة التدخلية بشكل مستقل عن تأثير المرض النفسي . ويمكن تفسير النتائج في سياق التحول التمثيلي إلى الامومه اثناء الحمل. وتقدم النتائج دليلا أوليا علي امكانيه اجراء استبيان جديد لتمثيلات الرعاية كاداه للكشف عن مخاطر التمثيلات أو التصورات الذهنية قبل الولادة.